KARAKTER MORFOLOGIS DAN PERKEMBANGAN ANATOMIS BIJI MELINJO (Gnetum gnemon L.) - Kandida Prajnaparamita; Siti Susanti (Program Studi Pendidikan Biologi, 2021)
Melinjo seeds (Gnetum gnemon L.) have many benefits, that it is necessary to know its morphological and anatomical characters. This study aimed to determine differences in morphological characters and anatomical development of melinjo seeds at four seed maturity stages. The morphological observation was carried out based on the quantitative and organoleptic characteristics of the melinjo seeds: outer envelope, size, and the color of the middle envelope. Seed development was anatomically observed in slides prepared with a non-embedding method using a sliding microtome then observed through a microscope. The outer seed envelope has a green to blackish-red color in the final stage, while the seed middle envelope has a light-brown to dark-brown in the final stage. The inner seed envelope is thin, non-rigid, and attached on the outside of the endosperm. The seeds' length ranges from ±1,5 cm until ±2,25 cm at the end-stage; seeds width are 1 cm – 1,18 cm; seeds diameter are 1 cm – 1,16 cm. The anatomical development showed tissue thickening and differentiation. The middle envelope is getting thicker: 318,84 μm to 397,29 μm. Endosperm tissue cells undergo cell compaction as the seeds ripen. At the same time, embryonic tissue differentiation forms hypocotyl, epicotyl, and cotyledon.